Infinitesimal : how a dangerous mathematical theory shaped the modern world - Alexander, Amir (Scientific American/Farrar, Straus and Giroux, 2014)
Explores "the epic battle over a mathematical concept that shook the old order and shaped the world as we know it. On August 10, 1632, five leaders of the Society of Jesus convened in a somber Roman palazzo to pass judgment on a simple idea: that a continuous line is composed of distinct and limitlessly tiny parts. The doctrine would become the foundation of calculus, but on that fateful day the judges ruled that it was forbidden. With the stroke of a pen they set off a war for the soul of the modern world"--